2022
DOI: 10.1002/adom.202102542
|View full text |Cite
|
Sign up to set email alerts
|

Facile, Real‐Time Identification of Blood Components with Self‐Powered Organic–Inorganic Heterostructure Photodetectors

Abstract: Yong-in, South Korea) for enhancing the wettability of the surface. The contact angles of various blood samples on surface-modified quartz were analyzed with a contact angle meter (DSA 100, KRUSS, Hamburg, Germany) (Figure S13, Supporting Information).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The aforementioned changes in junction properties were further elucidated through IS analyses conducted on devices B9, G9, and F9, representing low, medium, and high reverse currents (Figure 1h). The rectifying behavior of the PN diode is correlated with its depletion characteristics, which can be denoted by a parallel plate capacitor model as follows: [35] Junction capacitance…”
Section: Resultsmentioning
confidence: 99%
“…The aforementioned changes in junction properties were further elucidated through IS analyses conducted on devices B9, G9, and F9, representing low, medium, and high reverse currents (Figure 1h). The rectifying behavior of the PN diode is correlated with its depletion characteristics, which can be denoted by a parallel plate capacitor model as follows: [35] Junction capacitance…”
Section: Resultsmentioning
confidence: 99%
“…For biomaterials, Yoo's research team demonstrated the identification of blood components using an optoelectrical biosensor in 2022. [141] The light absorbance of white blood cells (WBC) and red blood cells (RBC) in the UV region is different. To identify the WBC and RBC in the blood, they constructed a sensing system as shown in Figure 9c.…”
Section: Chemical and Biological Analysismentioning
confidence: 99%
“…c) Chemical and biological analysis system based on UV PD. Adapted with permission from [141]. Copyright 2022, WILEY-VCH.…”
mentioning
confidence: 99%